Cost effectiveness of epidural steroid injections to manage chronic lower back pain - Whynes, David K.; McCahon, Robert A.; Ravenscroft, Andrew; Hardman, Jonathan (BioMed Central, 2012)
Background The efficacy of epidural steroid injections in the management of chronic low back pain is disputed, yet the technique remains popular amongst physicians and patients alike. This study assesses the cost effectiveness of injections administered in a routine outpatient setting in England.